Body image assessment and quality of life in patients with atopic dermatitis - Joanna Mikołajczyk; Teresa Rzepa; Joanna Król; Ryszard Żaba (Termedia Publishing House, 2017)
Introduction . Atopic dermatitis is a chronic and recurrent inflammatory skin condition. Significant skin lesions caused by the condition contribute to a negative perception of one's body. A negative body image may cause or enhance negative mental state, which, in a vicious circle, contributes to aggravation of the disease symptoms and deterioration of life quality. Especially skin lesions occurring on visible parts of the body may lead to a lack of acceptance by other people. Objective . To determine the impact of body image on the life quality evaluation of patients with atopic dermatitis. Material and methods. The study included 59 patients (36 women and 23 men) with atopic dermatitis. The patients completed the Multidimensional Body-Self Relations Questionnaire, which measures the general body image perception, the Dermatology Quality of Life Index and a personal survey. Results and conclusions . Among the patients with atopic dermatitis, the general body image evaluation was not correlated with the perceived life quality, though some statistically significant correlations were found between this variable and four body image dimensions. No statistically significant differences were found between men and women with regard to life quality assessment, but it was found that the women differed from the men statistically significantly with regard to the following dimensions of body image: Health Orientation (p = 0.0344) and Overweight Preoccupation (p = 0.0155). Moreover, illness duration was shown to have an impact on life quality assessment as well as on the two following dimensions of body image: Appearance Orientation and Health Evaluation.